Strategi Harian Kompas Dalam Membangun Brand Engagement NFT Kompas Melalui Aktivitas Community Relation - Kontessa, Tarrence Karmelia; Layardi, Hendy (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2024)
Digital transformation is something that most industrial players have done and continue to do. Transformation is carried out, through the use of the latest technology products such as non-fungible tokens (NFT). The popularity of NFTs, has grown rapidly and has become a hot topic of conversation in Indonesia. Kompas Daily as the largest national media in Indonesia has introduced NFT products through the Narasi Fakta Terkurasi (NFT Kompas) project since June 28, 2022. This project started with a decision to explore new business potential within the Kompas Gramedia Group. The boom in crypto, NFT and metaverse in early 2022 is considered as a great potential to develop the business. To support the Kompas NFT project, Kompas Daily is building a community and holding various activities as an effort to build Kompas NFT brand engagement. This research first adapts the Community Involvement concept by Lakin & Scheubel (2017) to understand Kompas' daily strategy, especially in building brand engagement in the Kompas NFT online community on the Discord channel. It was concluded that Kompas' NFT technology products had received a positive response and were able to build brand engagement in the NFT community which had the potential to become a new audience for Kompas Daily. Second, through Everett M. Rogers' diffusion-of-innovation theory, the research also explores the socialization strategy for Kompas NFT products. It was concluded that the exhibition forums, media articles and Townhall Meetings held by Kompas Daily to encourage the adoption of NFT innovation internally and externally to the company, were effective strategies for building audience adaptation to Kompas NFTs. This qualitative research using can be developed further, especially to examine more deeply community relations strategies for new technology products that are increasingly appearing in this digital era.ABSTRAKTransformasi digital adalah sebuah tuntutan peradaban yang antara lain dilakukan melalui penggunaan produk-produk teknologi terbaru seperti non-fungible token (NFT). Harian Kompas sebagai media nasional terbesar di Indonesia telah memperkenalkan produk NFT melalui proyek Narasi Fakta Terkurasi Kompas (NFT Kompas) sejak 28 Juni 2022. Untuk mendukung proyek NFT Kompas, Harian Kompas membangun komunitas dan mengadakan berbagai aktivitas sebagai upaya membangun brand engagement NFT Kompas. Penelitian dilakukan dengan metode kualitatif deskriptif. Pengambilan data dilakukan dengan observasi, wawancara dan dokumen. Tujuan dari penelitian, pertama dengan mengadaptasi konsep Community Involvement oleh Lakin & Scheubel (2017) peneliti menganalisa strategi Harian Kompas dalam membangun brand engagement pada online community NFT Kompas di kanal Discord. Disimpulkan bahwa produk teknologi NFT Kompas telah mendapat respon positif dan berhasil membangun brand engagement pada komunitas NFT yang berpotensi menjadi audiens baru bagi Harian Kompas. Kedua, melalui kacamata teori difusi-inovasi Everett M. Rogers (2005), penelitian juga menggali strategi sosialisasi produk NFT Kompas. Disimpulkan bahwa wadah pameran, artikel media dan Townhall Meeting yang dilakukan Harian Kompas untuk mendorong adopsi inovasi NFT ke arah internal maupun eksternal perusahaan, menjadi strategi yang efektif untuk membangun adaptasi audiens terhadap NFT Kompas. Penelitian kualitatif ini dapat dikembangkan lebih lanjut khususnya untuk mengkaji lebih dalam strategi community relation bagi produk-produk teknologi baru yang semakin sering muncul di era digital ini.